SufB intein splicing in Mycobacterium tuberculosis is influenced by two remote conserved N-extein histidines. Issue 3 (31st March 2022) - Panda, Sunita; Nanda, Ananya; Sahu, Nilanjan; Ojha, Deepak K.; Pradhan, Biswaranjan; Rai, Anjali; Suryawanshi, Amol R.; Banavali, Nilesh; Nayak, Sasmita
Abstract: Inteins are auto-processing domains that implement a multistep biochemical reaction termed protein splicing, marked by cleavage and formation of peptide bonds. They excise from a precursor protein, generating a functional protein via covalent bonding of flanking exteins. We report the kinetic study of splicing and cleavage reaction in [Fe–S] cluster assembly protein SufB from Mycobacterium tuberculosis ( Mtu ). Although it follows a canonical intein splicing pathway, distinct features are added by extein residues present in the active site. Sequence analysis identified two conserved histidines in the N-extein region; His-5 and His-38. Kinetic analyses of His-5Ala and His-38Ala SufB mutants exhibited significant reductions in splicing and cleavage rates relative to the SufB wildtype (WT) precursor protein. Structural analysis and molecular dynamics (MD) simulations suggested that Mtu SufB displays a unique mechanism where two remote histidines work concurrently to facilitate N-terminal cleavage reaction. His-38 is stabilized by the solvent-exposed His-5, and can impact N–S acyl shift by direct interaction with the catalytic Cys1. Development of inteins as biotechnological tools or as pathogen-specific novel antimicrobial targets requires a more complete understanding of such unexpected roles of conserved extein residues in protein splicing.